VD_FINDINFO Jug / 2023 / 224 vom 5. Dezember 2022 - VD Tribunal cantonal (2022)
TENTATIVEDROIT PÉNAL, TRAITEMENT AMBULATOIRE, FIXATION DE LA PEINE, MEURTRE | 144 al. 1 CP, 22 ad 111 CP, 63 CP, 90 al. 2 LCR